Preparation and Electrochemical Behaviour of a Titanium-Based Lead Dioxide Cathode Used in The Microbial Fuel Cell - Chen, Shaohua; Wang, Jiaquan; Xia, Xuelan; Chen, Chen; Yang, Jinping; Zhu, Yan (Asian Journal of Chemistry, 2012)
In this paper, the electrochemical behaviours of a titanium-based b-PbO2 cathode and a carbon cloth electrode used in the microbial fuel cell were studied. Linear sweep voltammetry (LSV) curves and cyclic voltammetry (CV) curves indicated that the electrochemical behaviours measured in a titanium-based b-PbO2 electrode system was similar to the carbon cloth electrode's, it did not participate in the reaction in the microbial fuel cell, but a titanium-based b-PbO2 electrode current response values were three times higher than the carbon cloth electrode.Thus it had greater electrochemical activity and could speed up the denitrification reaction in the microbial fuel cell, thereby enhancing its electricity-generation and decontamination performance. Carbon cloth electrode's electrochemical impedance spectroscopy (EIS) patterns showed that its electrochemical activity was poor. The EIS patterns of a titanium-based b-PbO2 electrode showed that the capacitance arc radius in the beginning of the reaction solution system, was larger than that of the completion of the reaction system with the reduce of interface capacitance value. The results showed that the electrochemical performance of the titanium-based b-PbO2 cathode was increased in the solution when the microbial fuel cell reaction was stopped. This behaviour of the cathode demonstrated that the start of microbial fuel cell required for a period of time from the mechanism.